Biodiversity Conservation Education: An evaluation of Effects on Students’ Knowledge, Perception and Attitudes - Heavenlin, M.; Christy, I.Kanitha; Gunasekaran, Dr.C.; Rajkumar, V.; Chinnaraj, P. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The unsustainable exploitation of biodiversity by humanity has lead many of theearth’s natural resources to the brink of collapse. In order to reverse this trend, conservationeducationist should reduce biodiversity illiteracy among the society, especially youngergeneration. Students are the future generation of the world. To evaluate the knowledge andattitude of the school students in biodiversity, various analysis and awareness was carried out.In our contribution, we focused on finding the differences between primary school students’attitudes towards biodiversity between their demographic variables such as gender, classlevel, family type, type of school and family income. The sample consists of 814 studentsfrom 10 schools. Students of grades 7th, 8th and 9th were analysed. Data were evaluated withfactor analysis and SPSS. The study emphasizes on the necessity to impart education forstudents regarding biodiversity. According to the results of the analysis of students' point ofattitude towards biodiversity, in terms of variables; a significant differences were found infavour of students, female students, and students in joined family and parent’s educationstatus.